The Role of a Low Fermentable Oligosaccharides, Disaccharides, Monosaccharides, and Polyol Diet in Nonceliac Gluten Sensitivity - P. Priyanka; S. Gayam; J. T. Kupec (Gastroenterology Research and Practice)
Background. Nonceliac gluten sensitivity (NCGS) is a recently defined clinical entity characterized by intestinal and extraintestinal symptoms associated with gluten ingestion in individuals in whom celiac disease (CD) or wheat allergy (WA) has been excluded. Despite its name and definition, gluten has been shown to precipitate symptoms in only 16–30% of these patients. In addition to gluten, other components of wheat, including fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs), alpha-amylase trypsin inhibitors (ATIs) and wheat germ agglutinin have been implicated in the causation of the symptoms of NCGS, with FODMAPs garnering the most attention. We present a review of the existing literature evaluating the role of FODMAPs in NCGS symptomatology. Methods. A systematic review of PubMed, Cochrane, EMBASE, and Google Scholar for keywords fructans, non-celiac gluten sensitivity, NCGS, FODMAPs, and gluten-free diet (GFD) was conducted through a series of advanced searches. Articles related to the use of fructans or FODMAPs were analyzed. Results. FODMAPs were found to be associated with gastrointestinal and extraintestinal symptoms in NCGS. Conclusions. A low FODMAP diet has potential for improvement of clinical symptoms in NCGS. In addition, some evidence suggests an additional benefit to simultaneous adherence to both low FODMAP diet and GFD.